2015
DOI: 10.1016/j.jns.2015.06.028
|View full text |Cite
|
Sign up to set email alerts
|

GM1 ganglioside in Parkinson's disease: Pilot study of effects on dopamine transporter binding

Abstract: Objective GM1 ganglioside has been suggested as a treatment for Parkinson’s disease (PD), potentially having symptomatic and disease modifying effects. The current pilot imaging study was performed to examine effects of GM1 on dopamine transporter binding, as a surrogate measure of disease progression, studied longitudinally. Methods Positron emission tomography (PET) imaging data were obtained from a subset of subjects enrolled in a delayed start clinical trial of GM1 in PD1: 15 Early-start (ES) subjects, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 45 publications
(58 reference statements)
0
37
0
Order By: Relevance
“…Administration of GM1 has been found to be beneficial for Parkinson patients ( 9 ), and the high fraction of GM1 in neurons has been correlated with their plasticity and axonal growth (see Ref. ( 4 ) and references therein).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of GM1 has been found to be beneficial for Parkinson patients ( 9 ), and the high fraction of GM1 in neurons has been correlated with their plasticity and axonal growth (see Ref. ( 4 ) and references therein).…”
Section: Resultsmentioning
confidence: 99%
“…GM1 plays a crucial role in connection with receptor proteins for cell-cell communication and can be found at high concentrations in the central nervous system of mammals. It strongly influences neural plasticity ( 4 ), was recently recognized as a factor in slowing down the progression of Parkinson disease ( 9 ), and is involved in a large number of essential functions in the plasma membrane and intracellular loci (for a recent review, see Ref. ( 10 )).…”
Section: Introductionmentioning
confidence: 99%
“…Past clinical trials for the treatment of other conditions have shown that GM1 administration in patients is relatively safe (Alter, ; Chinnock & Roberts, ; Schneider et al , , ). In spite of poor permeability of the blood–brain barrier to GM1 (Ghidoni et al , ; Saulino & Schengrund, ), sustained benefits of GM1 were observed in a small randomized double‐blind placebo‐controlled trial in Parkinson's disease patients even when this ganglioside was administered by subcutaneous injections (Schneider et al , , , ). Potential drug delivery challenges in HD patients could be circumvented through intrathecal (or intraventricular) drug administration, as in recent clinical trials with antisense oligonucleotides, or with strategies and formulations to improve drug delivery to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Probably the reason is that these clinical trials included peripheral administration of the ganglioside, which inefficiently permeates through the BBB. Although the BBB has been reported to be dysfunctional [12,13,[72][73][74][75][76], it remains a huge obstacle to adequate drug delivery to the brain.…”
Section: Discussionmentioning
confidence: 99%